Pengaruh Pemasaran Online Terhadap Volume Penjualan, Keuntungan Produk Olahan Tepung CV. Prasodjo Godean Sleman Yogyakarta - Prasetyo, Tegar Ari; Suprihanti, Antik (Universitas Batangahari Jambi, 2024)
CV. Prasodjo in the Godean District is one of the industries that utilize online marketing. This research aims to 1) analyze the level of sales growth and profit of CV. Prasodjo's processed flour products, 2) compare the sales of these products before and after using online marketing, 3) compare profit levels of these products before and after using online marketing, 4) and analyze the differences in sales of processed flour products dumpling skin, dim sum skin, spring roll skin, and egg noodles. This research employs a quantitative research method with the techniques of sales growth rate analysis, two-sample t-tests, and ANOVA analysis. The research results indicate that the sales growth and profit levels of CV. Prasodjo after implementing online marketing consistently shows positive values. The sales of CV. Prasodjo after using online marketing is higher than before implementing online marketing, and the profit after using online marketing is also greater than before using online marketing. Furthermore, the sales of processed flour products at CV. Prasodjo specifically dumpling covers are greater than the sales of dim sum covers, spring roll covers, and egg noodles.